Kommentare zur Taxonomie der Symphyta (Hymenoptera). (Vorarbeiten zu einem Katalog der Pflanzenwespen, Teil 1). - Taeger, Andreas; Blank, Stephan M. (Contributions to Entomology = Beiträge zur Entomologie, 1996)
In the course of preliminary studies for a catalogue of sawflies (Hymenoptera: Symphyta) nomenclatural problems are clarified. The type species of the genera Dolerus Panzer, 1801, Mesoneura Hartig, 1837, and Nematinus Rohwer, 1911 are designated and Dolerus (Equidolerus) subgen. nov. is described (= Dosytheus auct.). The following new synonyms of generic names are indicated: Croesus Curtis, 1824, syn. nov. (= Craesus Leach, 1817); Dosytheus Leach, 1817, syn. nov. (= Dolerus Panzer, 1801); Phaenusa Cameron, 1875, syn. nov. and Phoenusa Ed. André, 1880, syn. nov. (= Fenusa Leach, 1817); Pristis Brullé, 1846, syn. nov. (= Mesoneura Hartig, 1837); Anatoliroa Muche, 1983, syn. nov. (= Seljukia Benson, 1966). Messa Leach, 1817 cannot be interpreted. Fenusella Enslin, 1912 has to be used for Messa auct. Within the species-group 24 nominal taxa are synonymized and 24 new combinations are proposed (cf. index). The following replacement names are proposed: Tenthredo fredericki nom. nov. pro T. fallax F. Smith, 1878; T. compressicornuta nom. nov. pro T. compressicornis Cameron, 1899; T. clavicornuta nom. nov. pro T. clavicornis Konow, 1898; T. kuznetzovi nom. nov. pro Tenthredella eximia Kuznetzov-Ugamskij, 1927. The Symphyta described by F. Klug are listed with their correct original citations. Species lists for Aglaostigma W. F. Kirby, 1882, Craesus Leach, 1817, and Fenusella Enslin, 1912 are presented. Keywords Tenthredinidae, designation of type species, replacement names, new combinations, new synonyms, new subgenus, dates of publications. Nomenclatural Acts alpinum (Thomson, 1871) (Aglaostigma), comb. n. hitherto Perineura alpina sinicum (Takeuchi, 1940) (Aglaostigma), comb. n. hitherto Laurentia sinica anatolica Muche, 1983 (Anatoliroa), syn. n. of Seljukia tenebrosa Benson, 1966 singularis (Malaise, 1931) (Conaspidia), comb. n. hitherto Eriocampa singularis Equidolerus Taeger & Blank, 1996 (Dolerus), sgen. n. konowi Lacourt, 1989 (Elinora), syn. n. of Elinora maculipes (Lepeletier, 1823) maculipes (Lepeletier, 1823) (Elinora), comb. n. hitherto Tenthredo maculipes pallidipes (Dalla Torre, 1894) (Elinora), comb. n. hitherto Allantus pallidipes plana (Jakovlel, 1892) (Empria), comb. n. hitherto Poecilosoma plana alaskana (Kincaid, 1900) (Fenusella), comb. n. hitherto Fenusa alaskana glaucopsis (Konow, 1907) (Fenusella), comb. n. hitherto Fenusa glaucopsis hortulana (Klug, 1818) (Fenusella), comb. n. hitherto Tenthredo (Emphytes) hortulana javana (Enslin, 1912) (Fenusella), comb. n. hitherto Messa javana leucostoma (Rohwer, 1910) (Fenusella), comb. n. hitherto Parabates leucostoma nana (Klug, 1816) (Fenusella), comb. n. hitherto Tenthredo (Allantus) nana populifoliella (Townsend, 1893) (Fenusella), comb. n. hitherto Blennocampa populifoliella septentrionalis (Koch, 1990) (Fenusella), comb. n. hitherto Messa septentrionalis taianensis (Xiao & Zhou, 1983) (Fenusella), comb. n. hitherto Messa taianensis xylostei (Vallot, 1836) (Hoplocampoides), comb. n. hitherto Tenthredo xylostei matsumurai (Vikberg, 1982) (Nematinus), comb. n. hitherto Nematus matsumurai acuminatus Vikberg, 1982 (Nematus), syn. n. of Nematus acuminatus (Lindquist, 1968) brunnescens Vikberg, 1983 (Nematus), syn. n. of Nematus brunneus (Lindquist, 1971) glaber Vikberg, 1982 (Nematus), syn. n. of Nematus politus (Lindquist, 1974) squamicauda Vikberg, 1982 (Nematus), syn. n. of Nematus caudalis (Lindquist, 1968) truncicollis Vikberg, 1982 (Nematus), syn. n. of Nematus curticornis (Lindquist, 1969) berolinensis Muche, 1971 (Pachynematus), syn. n. of Amauronematus humeralis (Lepeletier, 1823) xylostei Giraud, 1863 (Selandria), syn. n. of Hoplocampoides xylostei (Vallot, 1836) excellens Kuznetzov-Ugamskij, 1927 (Tenthredella), syn. n. of Tenthredo tumida (Mocary, 1909) Anatoliroa Muche, 1983 (Tenthredinidae), syn. n. of Seljukia Benson, 1966 Craesus Leach, 1817 (Tenthredinidae), stat. rev. the name "Croesus Curtis, 1824" is an unjustified emandation Croesus Curtis, 1824 (Tenthredinidae), syn. n. of Craesus Leach, 1817 (unjustified emandation) Dosytheus Leach, 1817 (Tenthredinidae), syn. n. of Dolerus (Dolerus) Panzer, 1801 Fenusella Enslin, 1912 (Tenthredinidae), gen. rev. not a synonym of Messa Leach, 1817 Phaenusa Cameron, 1875 (Tenthredinidae), syn. n. of Fenusa Leach, 1817 (unjustified emendation) Phoenusa Ed. André, 1880 (Tenthredinidae), syn. n. of Fenusa Leach, 1817 (unjustified emendation) Selandria (Pristis) Brullé, 1846 (Tenthredinidae), syn. n. of Mesoneura Hartig, 1837 amplicapitata Zombori, 1974 (Tenthredo), syn. n. of Tenthredo (Tenthredella) stigma (Forsius, 1918) cameroni Malaise, 1945 (Tenthredo), syn. n. of Tenthredo (Olivacedo) ebba Benson, 1914 kerketa Dovnar-Zapolskij, 1930 (Tenthredo), syn. n. of Tenthredo (Tenthredo) albiventris albiventris (Mocsáry, 1880) pappi Zombori, 1978 (Tenthredo), syn. n. of Tednthredo (Olivacedo) eduardi Enslin, 1920 sortitor Malaise, 1938 (Tenthredo), syn. n. of Tenthredo (Tenthredella) abdominalis (Matsumura, 1912) stubbei Koch, 1984 (Tenthredo), syn. n. of Tenthredo (Tenthredella) borea Enslin, 1920 vinimalis Fallén, 1808 (Tenthredo), syn. n. of Trichiocampus grandis (Lepeletier, 1823); praeocc. by vinimalis Schrank, 1796 vivida Malaise, 1931 (Tenthredo), syn. n. of Tednthredo (Olivacedo) eduardi Enslin, 1920 fredericki Taeger & Blank, 1996 (Tenthredo (Olivacedo)), nom. n. pro Tenthredo fallax F. Smith, 1878, nec Lepeletier, 1823 hybrida Erichson, 1851 (Tenthredo (Poecilostoma)), nom. praeocc.; syn. n. of Tenthredo hybrida Evdersmann, 1847; now a synonym of Empria plana (Jakovlev, 1892) abdominalis (Matsumura, 1912) (Tenthredo (Tenthredella)), comb. n. hitherto Tenthredopsis abdominalis compressicornuta Taeger & Blank, 1996 (Tenthredo (Tenthredella)), nom. n. pro Tenthredo compressicornis Cameron, 1899, nec Fabricius, 1804 brunnea (Cameron, 1899) (Tenthredo (Tenthredina)), comb. n. hitherto Allantus brunneus clavicornuta Taeger & Blank, 1996 (Tenthredo (Tenthredo)), nom. n. pro Tenthredo clavicornis Konow, 1898, nec Fabricius, 1781 kuznetzovi Taeger & Blank, 1998 (Tenthredo (Tenthredo)), nom. n. pro Tenthredella eximia Kuznetzov-Ugamskij, nec Norton, 1868 nivosa (Klug, 1817) (Tenthredopsis), comb. n. hitherto Tenthredo (Allantus) nivosa grandis (Lepeletier, 1823) (Trichiocampus), comb. n. hitherto Nematus grandis